Health-related quality of life postventral hernia repair: Retrospective analysis - Abdulaziz Shaher; Hassan Mashbari; Abdallah Alferdaus; Shaima Yahya Ali Al-Hamdan; Rand Abduallah; Sharefah Ahmed Y Alabdullah; Raneem Mushabab Al-Murayeh; Amjad Abdulrahman Alqahtani; Walaa Muteb Alahmari (International Journal of Abdominal Wall and Hernia Surgery)
Abstract BACKGROUND: Laparoscopy has gained widespread adoption for ventral hernia repair, mirroring the trend seen in numerous intra-abdominal surgical procedures. The objective of this study was to evaluate the quality of life (QoL) of patients who underwent laparoscopic versus open surgical repair. MATERIALS AND METHODS: Patients who underwent surgery between January 2020 and December 2022 were included in this time-bound study. Of the 202 patients who underwent hernial repair over 3 years, all eligible patients were contacted and invited to participate in the study. The response rate was 77%, 155 patients completed the study questionnaire, which collected sociodemographic data, as well as the EORTC QLQ-C30 version 3.0 questionnaire, which assessed QoL. RESULTS: The mean age of the participants was 47.0 ± 13.0 years, with a range from 15.0 to 76.0 years. Among them, 67.7% were female, and 60.0% had comorbidities. Additionally, a lower proportion of laparoscopic cases required drain placement compared with the open group (12.9% vs. 26.9%). Patients who underwent laparoscopic surgery had shorter hospital stays within “1 day” (46.8% vs. 36.6%) or “2 days” (22.6% vs. 19%) and experienced a quicker return to activity, with a higher proportion resuming normalcy after 2 weeks (27.4% vs. 20.4%). Furthermore, patients in the open group reported higher pain scores, higher constipation, and insomnia scores than those in the laparoscopic group. CONCLUSIONS: This study showed that laparoscopic repair had fewer complications than open repair in terms of hospital stay, return to activities, and pain score. Regarding the QoL scale, the laparoscopic approach shows a far better QoL profile compared with the open technique.